Tradeoffs between chilling and forcing in satisfying dormancy requirements for Pacific Northwest tree species - Harrington, Constance A.; Gould, Peter J. (Frontiers in Plant Science, 2015)
Many temperate and boreal tree species have a chilling requirement, that is, they need to experience cold temperatures during fall and winter to burst bud normally in the spring. Results from trials with 11 Pacific Northwest tree species are consistent with the concept that plants can accumulate both chilling and forcing units simultaneously during the dormant season and they exhibit a tradeoff between amount of forcing and chilling. That is, the parallel model of chilling and forcing was more effective than the sequential model and well chilled plants require less forcing for bud burst than plants which have received less chilling. Genotypes differed in the shape of the possibility line which describes the quantitative tradeoff between chilling and forcing units. Plants which have an obligate chilling requirement (Douglas-fir, western hemlock, western larch, pines, true firs) and received no or very low levels of chilling did not burst bud normally even with long photoperiods. Pacific madrone and western redcedar benefited from chilling in terms of requiring less forcing to promote bud burst but many burst bud normally without chilling. Equations predicting budburst were developed for each species in our trials for a portion of western North America under current climatic conditions and for 2080. Mean winter temperature was predicted to increase 3.2 to 5.5 °C and this change resulted in earlier predicted budburst for Douglas-fir throughout much of our study area (up to 74 days earlier) but later budburst in some southern portions of its current range (up to 48 days later) as insufficient chilling is predicted to occur. Other species all had earlier predicted dates of budburst by 2080 than currently. Recent warming trends have resulted in earlier budburst for some woody plant species; however, the substantial winter warming predicted by some climate models will reduce future chilling in some locations such that budburst will not consistently occur earlier.